Helical ullazine-quinoxaline-based polycyclic aromatic hydrocarbons - Richter, Marcus; Hahn, Sebastian; Rominger, Frank; Bunz, Uwe H. F. (Chemistry - a European journal, 2019)
Polycyclic aromatic azomethine ylides (PAMYs) are powerful building blocks in the bottom-up synthesis of internally nitrogen-containing polycyclic aromatic hydrocarbons (N-PAHs) through 1,3-cycloaddition reactions. In this work, the cycloaddition reaction of PAMYs to asymmetric ortho-quinones is presented, which, in contrast to the addition to symmetric para-quinones, facilitates subsequent condensation reactions and allows the synthesis of three helical N-PAHs with ullazine-quinoxaline (UQ-1-3) backbones. UQ-1 and UQ-2 possess two helical centers; however, single-crystal X-ray analysis together with the computational modeling of UQ-3 elucidate the formation of only the thermodynamically most stable geometry with four helical centers in a (P,P,M,M) configuration. For the series UQ-1-3, the number of redox steps is directly correlated with the number of ullazine or quinoxaline units incorporated into the targeted molecular backbones. A detailed investigation of the spectroscopic and magnetic properties of the radical cation and anion as well as the dication and dianion species by in situ EPR/UV/Vis-NIR spectroelectrochemistry is provided. The excellent optical and redox properties combined with helical geometries render them possibly applicable as chiral emitter or ambipolar charge transport material in organic electronics.